Gold-Based Metal Drugs as Inhibitors of Coronavirus Proteins: The Inhibition of SARS-CoV-2 Main Protease by Auranofin and Its Analogs - Lara Massai; Deborah Grifagni; Alessia De Santis; Andrea Geri; Francesca Cantini; Vito Calderone; Lucia Banci; Luigi Messori (Biomolecules, 2022)
Gold compounds have a long tradition in medicine and offer many opportunities for new therapeutic applications. Herein, we evaluated the lead compound Auranofin and five related gold(I) complexes as possible inhibitors of SARS-CoV-2 Main Protease (SARS-CoV-2 Mpro), a validated drug target for the COVID-19 disease. The investigational panel of gold compounds included Auranofin; three halido analogues, i.e., Au(PEt3)Cl, Au(PEt3)Br, and Au(PEt3)I; and two gold carbene complexes, i.e., Au(NHC)Cl and [Au(NHC)2]PF6. Notably, all these gold compounds, with the only exception of [Au(NHC)2]PF6, turned out to be potent inhibitors of the catalytic activity of SARS-CoV-2 Mpro: the measured Ki values were in the range 2.1–0.4 μM. The reactions of the various gold compounds with SARS-CoV-2 Mpro were subsequently investigated through electrospray ionization (ESI) mass spectrometry (MS) upon a careful optimization of the experimental conditions; the ESI MS spectra provided clear evidence for the formation of tight metallodrug-protein adducts and for the coordination of well defined gold-containing fragments to the SARS-CoV-2 Mpro, again with the only exception of [Au(NHC)2]PF6, The metal-protein stoichiometry was unambiguously determined for the resulting species. The crystal structures of the metallodrug- Mpro adducts were solved in the case of Au(PEt3)Br and Au(NHC)Cl. These crystal structures show that gold coordination occurs at the level of catalytic Cys 145 in the case of Au(NHC)Cl and at the level of both Cys 145 and Cys 156 for Au(PEt3)Br. Tight coordination of gold atoms to functionally relevant cysteine residues is believed to represent the true molecular basis of strong enzyme inhibition.